A new Amazonian species of Rhaebo (Anura: Bufonidae) with comments on Rhaebo glaberrimus (Günther, 1869) and Rhaebo guttatus (Schneider, 1799) - Mueses-Cisneros, Jonh Jairo; Cisneros-Heredia, Diego F.; Mcdiarmid, Roy W. (Zootaxa, 2012)
We describe a new species of toad of the genus Rhaebo from the Amazonian lowlands of Colombia and Ecuador. The newspecies is characterized by have a large-size (SVL 156.7 mm in adult female, 92.8–127.0 mm in adult males), lacking apreocular ridge and most cephalic crests except for the low parietals crests; having the cloacal opening towards the middlelevel of thighs; rounded to slightly oval parotoids; and dark to cream brown groin. The new species was previouslyconfused with Rhaebo glaberrimus, but the latter differs by having the cloacal opening at the ventral level of the thighs,small body size, skin texture mainly smooth, and a pink or yellowish color in the groin. The new species is also similar toRhaebo guttatus that differs by having a preocular ridge and a different ventral coloration (throat, chest and belly withcream round spots). We also comment on the identity of R. glaberrimus and R. guttatus, correct some reports published in the literature, and present new information on their natural history and distribution.